2019
DOI: 10.1101/709055
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Short-term oxaliplatin exposure according to established hyperthermic intraperitoneal chemotherapy (HIPEC) protocols lacks effectivenessin vitroandex vivo

Abstract: Key Points: Oxaliplatin (OX)-containing solutions obtained during patient treatment with Hyperthermic intraperitoneal chemotherapy (HIPEC) unexpectedly showed low cytotoxicity in an impedance-based ex vivo cytotoxicity cell assay.  OX cytotoxicity under HIPEC conditions could be enhanced by extending drug exposure to one hour by an impedance-based ex vivo cytotoxicity cell assay.  HIPEC failed to show survival benefits in the randomized controlled PRODIGE 7 trial and was questioned in the aftermath.  Clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…For example, Kirstein et al showed that the combination of heat (42 °C) and oxaliplatin was significantly more effective at a treatment duration of 2 h compared to 30 min [ 11 ]. This was underlined by the study performed by Löffler et al, concluding that 30-min exposure to clinical oxaliplatin concentrations frequently fails to induce 50% cell death and that oxaliplatin should be applied longer for generating an adequate amount of cell death [ 107 ]. In a different study by Murata et al three different gastric cancer cell lines were treated with either 5-FU, mitomycin C or cisplatin for a duration of 30 or 60 min.…”
Section: Physiological and Anticancer Aspects Of Preclinical Hipec Modelsmentioning
confidence: 99%
“…For example, Kirstein et al showed that the combination of heat (42 °C) and oxaliplatin was significantly more effective at a treatment duration of 2 h compared to 30 min [ 11 ]. This was underlined by the study performed by Löffler et al, concluding that 30-min exposure to clinical oxaliplatin concentrations frequently fails to induce 50% cell death and that oxaliplatin should be applied longer for generating an adequate amount of cell death [ 107 ]. In a different study by Murata et al three different gastric cancer cell lines were treated with either 5-FU, mitomycin C or cisplatin for a duration of 30 or 60 min.…”
Section: Physiological and Anticancer Aspects Of Preclinical Hipec Modelsmentioning
confidence: 99%
“…As convincing preclinical evidence to inform clinical practice remains the exception such research frequently post-dates the clinical use of drugs for HIPEC (cf. studies with oxaliplatin [12,13] or mitomycin C (MMC) [14]).…”
Section: Hyperthermic Intraperitoneal Chemotherapymentioning
confidence: 99%
“…Aiming to compile evidence to understand the underlying mechanisms for failure of certain HIPEC protocols, our group has recently gathered preliminary evidence (available as a preprint) suggesting that during short-term HIPEC, oxaliplatin is unable to penetrate deep enough into cell layers (~100 µm) to cause relevant cell death even in micrometastases [12]. Likewise, Ubink et al have evaluated clinically used HIPEC protocols in an in vitro CRC organoid model [13], where both MMC and oxaliplatin were shown ineffective to induce robust cell death at commonly attained drug dosages reached during HIPEC in vivo, suggesting there may be more generic issues.…”
Section: Is Oxaliplatin the Wrong Drug For Hipec?mentioning
confidence: 99%